Analysis the impact of ground conductivity source current speed and source current rise time on peak induced voltage on overhead conductors - Md. Kamal Hossain; Lima Tasnim (Discover Electronics)
Abstract The paper presents a finite element modeling approach to analyze lightning-induced voltages (LIV) on overhead conductors, focusing on factors such as the distance from the strike point, ground conductivity, source current speed, and current rise time. Firstly, the return stroke current (RSC) at various altitudes throughout the lightning path and the electromagnetic field radiation surrounding the strike point have been thoroughly examined. Secondly, the influence of ground conductivity on peak-induced LIV on overhead conductor, with specific numerical findings (e.g., peak-induced voltages reaching 109.9 kV at 40 m horizontal distance from the strike point for finite ground conductivity; at the same horizontal distance, peak-induced voltages reaching 95.9 kV for infinite ground conductivity). Thirdly, it is observed that at different horizontal distances from the strike point, the peak-induced voltages on overhead conductors increase if the source current speed increases. Additionally, the impact of source current rise time on peak-induced voltages of an overhead conductor has been noted and found that if the source current rise time increases, peak-induced voltages decrease. When developing an overhead conductor protection strategy and creating a mechanism of failure, the suggested model and analysis would be helpful.